2018
DOI: 10.1080/1369118x.2018.1428651
|View full text |Cite
|
Sign up to set email alerts
|

Does compassion go viral? Social media, caring, and the Fort McMurray wildfire

Abstract: In May 2016, an enormous wildfire threatened the city of Fort McMurray, Alberta and forced the evacuation of all of the city's residents. Outpourings of support teemed in from all across Canada and over the world, prompting the largest charitable response in Canadian Red Cross history. This paper examines Albertans' response to the wildfire by exploring caring and helping behaviors as well as the role of social media in facilitating these remarkable charitable efforts. The paper uses mixed methods including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 35 publications
2
49
0
Order By: Relevance
“…For example, Carroll and colleagues [45] found that after the Rodeo-Chediski fire in the U.S., residents helped neighbours by providing shelter and support. In this case, the substantial amount of help provided to evacuees from residents in other communities within RMWB, elsewhere in Alberta, and beyond may be due to the number of people who evacuated, the extensive use of social media and media coverage of this wildfire [48].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Carroll and colleagues [45] found that after the Rodeo-Chediski fire in the U.S., residents helped neighbours by providing shelter and support. In this case, the substantial amount of help provided to evacuees from residents in other communities within RMWB, elsewhere in Alberta, and beyond may be due to the number of people who evacuated, the extensive use of social media and media coverage of this wildfire [48].…”
Section: Discussionmentioning
confidence: 99%
“…Crisis points, such as terror attacks, create "information holes" that the public works collaboratively to fill in in real time (Lin, Lachlan, & Spence, 2016, p. 627). Such practices resonate more broadly with developments in which social media has come to be an important tool for disaster and crisis management among civilians as well as governments (Boulianne, Minaker, & Haney, 2018;Liu, Fraustino, & Jin, 2016;Murthy & Gross, 2017;Yates & Paquette, 2011).…”
Section: Introductionmentioning
confidence: 91%
“…Finally, social media could be used to increase social capital among community members after a disaster [78,79]. Social media platforms could assist recovering populations in developing a sense of community [80] and in turn manage their own recovery processes.…”
Section: Social Media For Post-disaster Relationship Developmentmentioning
confidence: 99%
“…• Social media could help journalists mediate recovery-focused discussions between affected communities and emergency managers [35]. • Social media could also assist in developing a sense of community and increase members' ability to manage their own recovery processes after a disaster event [78][79][80][81]. Additionally, unconventional stakeholders could become prominent disaster recovery actors with the help of social media [82].…”
Section: Summary Of Findings On the Use Of Social Media For Disaster mentioning
confidence: 99%
See 1 more Smart Citation